เซ็กส์กับแฟชั่น : วัตถุนิยม - สุนทรพิพิธ, นายพันธุ์ชนะ (Fine Arts Journal: Srinakharinwirot University, 2018)
In the world that everything money can buy. The possession of all the objects we desire giving us pleasure and satisfaction. Meanwhile, living in a society that both politic and economic pushing people to spend more money under the context of strengthen the nation, the propaganda in adding extra value into everything in our life becomes common and necessary. This is the reason why in capitalism world, we attract to something because of its beauty made by others, and we decide to purchase it because of the recommendation also made by others. In the world that everything money can buy. The possession of all the objects we desire giving us pleasure and satisfaction. Meanwhile, living in a society that both politic and economic pushing people to spend more money under the context of strengthen the nation, the propaganda in adding extra value into everything in our life becomes common and necessary. This is the reason why in capitalism world, we attract to something because of its beauty made by others, and we decide to purchase it because of the recommendation also made by others. The strange phenomenon of Fetishism that can trace back in time, shows us the power of objects over human, we adore them, and we worship them and for some people the objects becomes symbols of sexual representation. In spite of judging them as weirdo and sicko, if we try to understand how this phenomenon could happened, we might finally get the answer whether they are sick or it is all an act against the capitalism world we are living in.